FRI0114 Diagnostic value of nucleosome-specific antibodies in recent active non treated sle. (1st June 2001) - Goetz, J; Humbel, RL; Monier, JC; Cohen, J; Andre, C; Bacquey, A; Chevailler, A; Chretien, P; Escande, A; Johannet, C; Oskmann, F; Olsson, NO; et al.
Abstract : Background: The nucleosome is considered as a major antigen in SLE and nucleosome-specific antibodies (Ab) seem to be the most specific and the earliest markers of SLE. Objectives: To evaluate different methods of detecting anti-nucleosome Abs and determine the diagnostic value of these Abs in recently active SLE. Methods: A 2 year (1998–99) prospective multicenter study in 13 European Immunopathology Centres (Groupe d'Etude de l'Auto-Immunite). Patients: (i) 55 cases of recently active SLE (evolution < 1 year), (ii) 50 other autoimmune diseases: 31 RA, 15 primary SJÖGREN'S syndrome, 2 scleroderma, 2 unclassified connective tissue disease. IgG anti-nucleosome Abs were detected by ELISA or immunodot using different nucleosome preparations. IgG anti-ds DNA Abs were detected by ELISA (calf thymus and human recombinant plasmid DNA). Results: 34/55 SLE patients had anti-nucleosome Abs reacting with 4 kits. 16/55 SLE patients had anti-nucleosome Abs reacting with 1 to 3 kits. 5/55 SLE patients were negative for anti-nucleosome Abs. 5/50 patients with other autoimmune diseases had anti-nucleosome Abs. Conclusion: 50/55 (91%) of patients with recently active SLE had anti-nucleosome Abs (by at least 1 method), 46/55 (84%) also had anti-ds DNA Abs (by ELISA). The sensitivity and the specificity of the anti-nucleosome Abs for SLE depend on the method and the nucleosome preparation.